Juan Gonzalo Restrepo Londoño. Semblanzas de un empresario (2019)
This is a brief journey through the life of Juan Gonzalo Restrepo Londoño. Besides having the fortune of growing up within the heart of a traditional family of Antioquia, he became bearer of invaluable knowledge since his youth, which allowed him to engage successfully in the entrepreneurial machinery of the region during the second half of the XXth century.The institution of the family, the knowledge of the natural and social context and a marked tendency to serve the interests of a region would be, among others, the elements to characterize and make intelligible the actions of this versatile and innovative businessman.